Fluorine-Free Cycloaliphatic Epoxy-Based Siloxane Nanohybrid Binder with High Polar Hydroxyl Group Content Enabling LiFePO4-Type Battery with High Electrochemical Performance and Stability - Jeong, Uktae; Jang, Junho; Hwang, Young Geun; Kang, Dong Jun; Kang, Min Jeong; Yoo, Jung-Keun; Oh, Youngseok; Yi, Jin Woo; Yoon, Jihee; Im, Hyeon-Gyun (American Chemical Society, 2024)
LiFePO4-type (LFP) batteries have attracted significant attention in most battery manufacturing industries due to their long lifespan, high-temperature safety, and low cost of raw materials. However, as an active material, LFP still suffers from several intrinsic drawbacks, including poor conductivity, a low Li+ diffusion coefficient, low capacity, and a lack of electrochemical stability, primarily due to conventional fluorine-based binders. Here, we report a simple yet effective approach to developing a fluorine-free binder based on a robust cycloaliphatic epoxy-based siloxane nanohybrid material (CES) to achieve high electrochemical stability in LFP batteries. The high content of silanol moieties in CES induces a strong affinity for the active material and conductive agent, significantly improving rheological (thixotropy) and mechanical (adhesion and cohesion) properties, which enable the formation of a uniformly coated electrode. As a result, we achieved superior electrochemical performance and stability in CES-applied electrodes compared to those with conventional fluorine-based binders. We investigate the reasons behind the contribution of CES to the electrochemical stability of LFP batteries through various analyses. The high thermal and oxidation stability of CES effectively prevents degradation of LFP-based active materials. Our binder development strategy offers a significant breakthrough in replacing conventional fluorine-based binders, advancing the development of high-performance and stable secondary batteries.